Phytochemical Screening and In Vitro Antidiabetic Test of Ethyl Acetate Fraction of Tiger’s Betel (Piper porphyrophyllum) - Hanifah, Nurul; Santoni, Adlis; Efdi, Mai (Hydrogen: Jurnal Kependidikan Kimia, 2024)
Piper porphyrophyllum or known as tiger’s betel, is a medicinal plant of the Piper genus that is quite widespread in Indonesia, especially on Java, Sumatra, and Kalimantan island. Tiger’s betel is widely used traditionally to treat headaches, bone pain, chest tightness, skin diseases, relieve inflammation, and diabetes mellitus. This study aims to determine the type of secondary metabolite compounds contained in the ethyl acetate fraction of tiger’s betel and determine its antidiabetic activity. Determination of the type of compound is conducted by phytochemical screening by a qualitative test using various reagents to identify flavonoids, phenolics, saponins, triterpenoids, steroids, alkaloids, and coumarins. The antidiabetic assay was carried out by inhibiting α-glucosidase activity and the results were reported as IC50 values. The ethyl acetate fraction of tiger’s betel positively contains alkaloids, flavonoids, and phenolics. The antidiabetic activity is classified as very strong, with an IC50 value of 14.06 µg/mL.